Legal Protection Against Discriminatory Treatment of Persons with Disabilities in Procurement of Recruitment for State Civil Servants - Ghassani, Firasya Dhiwa; Amarini, Indrianti (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
UUD NRI 1945 Constitution emphasizes that the government must protect the rights of each individual, develop rules and implement them accurately and maintain justice for all levels of society without exception for people with disabilities. The recruitment process of the State Civil Apparatus in Indonesia has not been completely free from allegations of discrimination. The experience of drg Romi, a person with a disability from Solok Regency, is an example of the many cases of discrimination that occur in Indonesia. The UUPD explains the rights of persons with disabilities, by stating the obligations of the government and agencies in this regulation, the fulfillment of the rights of persons with disabilities can be fulfilled. The provisions regulated regarding the fulfillment of the rights of persons with disabilities in the recruitment process of the State Civil Apparatus in the ASN Law are the reference of this research. The author's research method is normative juridical or normative legal research using qualitative analysis methods to achieve the objectives of this writing.